Salivary eicosanoid concentration in patients with Sjögren's syndrome. Issue 3 (March 1996) - Tishler, M; Yaron, I; Raz, A; Meyer, F A; Yaron, M
Abstract : OBJECTIVE: To investigate eicosanoid concentrations in the saliva of patients with primary Sjögren's syndrome (SS). METHODS: Whole mixed saliva of 36 subjects was assayed for eicosanoid concentrations using a radioimmunoassay. Patients with primary SS having positive lip biopsy served as the study group; their results were compared with data from patients with dry mouth and negative lip biopsy (dry mouth group), and with a group of normal healthy controls. RESULTS: Concentrations of thromboxane B2 were significantly (p < 0.01) increased in 18 patients with primary SS compared with 10 patients with dry mouth and eight healthy normal controls (1.95 (SD 0.51) ng/ml saliva compared with 0.52 (0.1) ng/ml and 0.3 (0.1) ng/ml, respectively). Similarly, prostaglandin E2 concentrations were also significantly increased (p < 0.01) in 11 patients with primary SS compared with five patients with dry mouth and eight normal controls (3.75 (0.82) ng/ml saliva compared with 0.32 (0.1) ng/ml and 0.41 (0.1) ng/ml, respectively). CONCLUSION: Salivary concentrations of eicosanoids are significantly increased in patients with primary SS, and this may prove helpful in the diagnosis of this disease.